Leadership styles' influence on the quality of nursing care. Issue 6 (8th July 2019) - Alloubani, Aladeen; Akhu-Zaheya, Laila; Abdelhafiz, Ibrahim Mubarak; Almatari, M.
Abstract : Purpose: The purpose of this paper is to investigate managers' leadership styles, from the perspective of registered nurses, and its effects on the quality of nursing care in both the private and public healthcare sectors. An additional aim is to assess the relationship between leadership styles and particular organisational outcomes. Design/methodology/approach: The sample for this quantitative research study was comprised of 400 respondents, among which 50 were nurse managers, 150 were staff nurses and the remaining respondents were patients. Two questionnaires were used in this study: the multi-factor leadership questionnaire (MLQ) 5X short and a patient satisfaction with nursing care quality questionnaire (PSNCQQ). Findings: A positive correlation was found between the transformational leadership style with leadership outcomes and the quality of nursing care ( r =0.811**, 0.759**, 0.789** and 0.877** for extra effort, job satisfaction, leader effectiveness and quality, respectively). Practical implications: Although the sample study was extensive, a possible limitation is that the research utilised convenient sample who are working in the private and public healthcare sectors thus limiting the generalisability of the study. Originality/value: This study was proposed as a baseline for upcoming studies in areas of education, nursing practice, research and quality. Moreover, this study was expected to be imperative to the hospital's management, in order to improve the current level of leadership, education models and advancement programs for the healthcare sector's senior staff.